Making 3 Dimensional Animated Short Film The Book of Jonah for Children - Dunggio, Ricky Christofel; Mamahit, Dringhuzen J.; Karouw, Stanley D.S. (Universitas Sam Ratulangi, 2021)
Abstract — Multimedia not only provides a lot of text, but also animates the text accompanied by sound, images, music, animation and video. The 3D animated short film, the book of Yunus, is based on ideas and storylines that support 3D animation film production activities, 3D animated film production using a 3D animated short film research framework. In this day and age, many children prefer animated stories so the problem formulation that can be taken is how to make the story of the bible Jonah can be implemented through 3-dimensional animated films. Software used: Blender, MakeHuman, Filmora, Vegas pro. The design method used is the development method in which there are 3 stages of making 3-dimensional animated short films starting with the pre-production, production, and post-production stages. With the use of Multimedia, the delivery of information will be more attractive and make it easier for users to get information. Based on the objectives, this study presents and tells Yunus's story in the form of a 3-dimensional animated short film. So that the benefits of this 3 Dimensional Animated Short Film can be a medium for learning and getting to know how the story of the Prophet Yunus in the Book of Yunus. The conclusion is that with this animated film based on the bible story, especially the book of Jonah, children can get to know and be more interested in the bible story which is adopted into a 3-dimensional animated story. Keywords — Animation; Multimedia; Rendering; Software. Abstrak — Multimedia bukan hanya menyediakan banyak teks, melainkan juga dengan menghidupkan teks yang di sertai bunyi, gambar, musik, Animasi dan video. Film pendek animasi 3D kitab Yunus, didasarkan pada ide dan alur cerita yang mendukung kegiatan produksi film animasi 3D, produksi film animasi 3D menggunakan kerangka penelitian film pendek animasi 3D. Di zaman ini banyak anak-anak yang lebih menyukai cerita dalam bentuk animasi jadi rumusan masalah yang bisa diambil adalah Bagaimana membuat cerita alkitab Yunus bisa di implementasikan lewat Film animasi 3 dimensi. Software yang digunakan: Blender, MakeHuman, Filmora,Vegas pro. Metode perancangan yang digunakan adalah metode development yang didalamnya Terdapat 3 tahap pembuatan Film Pendek Animasi 3 Dimensi diawali dengan tahap pra produksi, produksi, hingga pasca produksi. Dengan penggunaan Multimedia, penyampaian informasi akan menjadi lebih menarik dan mempermudah pengguna dalam mendapat informasi. Berdasarkan Tujuannya, penelitian ini menampilkan dan menceritakan cerita Yunus dalam bentuk Film Pendek Animasi 3 Dimensi. Sehingga Manfaat dari Film Pendek Animasi 3 Dimensi ini dapat menjadi media untuk mempelajari dan mengenal bagaimana cerita dari Nabi Yunus dalam Kitab Yunus. Kesimpulannya dengan adanya film animasi yang di angkat dari cerita alkitab khususnya kitab Yunus ini, anak-anak bisa lebih mengenal dan tertarik dengan cerita alkitab yang di angkat menjadi sebuah cerita animasi 3 dimensi. Kata kunci — Animasi; Multimedia; Render; Software.